Aligned microfiber-induced macrophage polarization to guide schwann-cell-enabled peripheral nerve regeneration. (May 2021) - Dong, Xianhao; Liu, Siyang; Yang, Yueyue; Gao, Shan; Li, Wenlei; Cao, Jiasong; Wan, Ye; Huang, Ziqi; Fan, Guanwei; Chen, Quan; Wang, Hongjun; Zhu, Meifeng; et al.
Abstract: Mechanistic understanding of the topological cues delivered by biomaterials in promotion of oriented tissue regeneration ( e.g ., peripheral nerve regrowth) remains largely elusive. Here, we engineered nerve conduits composed of oriented microfiber-bundle cores and randomly organized nanofiber sheaths to particularly interrogate the regulatory mechanism of microfiber orientation on promoted peripheral nerve regeneration. With comprehensive yet systematic analyses, we were able to elucidate the intricate cascade of biological responses associated with conduit-assisted nerve regrowth, i.e ., oriented microfibers facilitated macrophage recruitment and subsequent polarization toward a pro-healing phenotype, which in turn promoted Schwann cell (SC) migration, myelinization and axonal extension. Pronounced improvement of nerve regeneration in rat sciatic nerve injury was evidenced with enhanced electrophysiologic function, sciatic functional index and alleviated muscle atrophy 3 months post-implantation. The obtained results offer essential insights on the topological regulation of biomaterials in functional nerve tissue regeneration via immune modulation.